EFEITO DA DESTILAÇÃO DA ÁGUA NA EXTRAÇÃO DE FLAVONOIDES ORIUNDOS DE CHÁ COMERCIAL - CASTRO, Thiago Luis Aguayo de Castro; LOUREIRO, Raquel Parra; MACHADO, Lucas Masaharu Hanaoka; GOMES, Luiz Rafael Silva; BOTTEGA, Fernanda Christina; CARDOSO, Claudia Andrea Lima (ANAIS DO ENIC, 2026)
.